Recombinant Plasminogen Activator of the Sandworm (Perinereis aibuhitensis) Expression in Escherichia coli - Tuo Song; Xiaozhen Diao; Jun Cheng; Yang Man; Boyu Chen; Haixing Zhang; Wenhui Wu (Bioengineering)
As an essential thrombolytic agent, the tissue plasminogen activator receives increasing attention due to its longer half-life, lower immunogenicity, and easier administration, which are superior to other thrombolytic agents. In this study, the isolated and purified plasminogen activator from the sandworm (Perinereis aibuhitensis) was expressed in E. coli (Escherichia coli) to investigate its potential for simplifying the development process. The sandworm plasminogen activator was previously successfully cloned and expressed in E. coli with low yield and activity in the culture supernatant. This low yield and activity prompted us to optimize its DNA sequence. Furthermore, to raise the efficiency in the separation of the target protein, the protein’s solubility was enhanced by fusing it with maltose-binding protein (MBP) tags. Eventually, the fibrinolytic activity was successfully restored after digestion with tobacco etch virus (TEV) protease. This study provides an innovative method of efficiently expressing and purifying plasminogen activators from sandworm in E. coli and broadens its applications in therapeutic treatment of cardiovascular diseases, including thrombosis, stroke, and coronary atherosclerotic heart disease.